1998
DOI: 10.1177/0265407598154001
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and Need Fulfillment in Couple Relationships

Abstract: Two studies were conducted to explore the following questions: (i) does intimacy, within the context of a couple relationship, contribute to individual need fulfillment?; (ii) does self-disclosure have beneficial effects on need fulfillment without being accompanied by intimacy's others dimensions: positive affective tone and partner listening and understanding?; and (iii) does intimacy's impact on need fulfillment mediate its relationship with physical and psychological well-being? For the first study, 154 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 24 publications
5
89
0
1
Order By: Relevance
“…Research has shown that intimacy is related to several positive aspects of a relationship, such as greater marital satisfaction (Greeff & Malherbe, 2001;Prager, 1995) and improvements in the psychological and physical health of each element of the dyad (Prager, 1995;Prager & Buhrmester, 1998). Prager (1995) argued that intimate relationships buffer the pathogenic effects of stress and provide several mental and physical health benefits.…”
Section: The Role Of Marital Intimacy In the Adjustment Of Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that intimacy is related to several positive aspects of a relationship, such as greater marital satisfaction (Greeff & Malherbe, 2001;Prager, 1995) and improvements in the psychological and physical health of each element of the dyad (Prager, 1995;Prager & Buhrmester, 1998). Prager (1995) argued that intimate relationships buffer the pathogenic effects of stress and provide several mental and physical health benefits.…”
Section: The Role Of Marital Intimacy In the Adjustment Of Partnersmentioning
confidence: 99%
“…Although the literature has consistently shown that marital intimacy has beneficial effects on individual health and well-being (Prager, 1995;Prager & Buhrmester, 1998) regardless of the presence or absence of a stressful life situation, a moderating effect of the group was found: the associations between marital intimacy and psychosocial adjustment were significant only among the partners of breast cancer patients (with the exception of social QoL, which was also related to intimacy among the partners of healthy woman, although the regression slope was much less pronounced). These results can be explained in the context of a life-threatening disease because intimate relationships, such as the marital relationship, often assume a more powerful role in determining individual well-being than in situations that lack such a threat (Bolger, Foster, Vinokur, & Ng, 1996).…”
Section: The Influence Of Marital Intimacy On the Psychosocial Adjustmentioning
confidence: 99%
“…Örneğin Prager ve Buhremester yakın ilişkide kendini açmayı ele almışlardır. [54] Araştırmada kendini açmanın bilme-bilinme ve duyguları ifade etme gibi gereksinim giderici bir işlevi olduğu sonucuna varılmıştır. Romantik ilişkilerde çatışma olgusunu araştıran Hojjat cinsiyetler arasında çatışma konusunda anlamlı bir farklılık bulmuştur.…”
Section: Discussionunclassified
“…'I express a need, wish, or want') from the self-disclosure scale of Prager and Buhrmester (1998). Cronbach's alpha was .82 at Time 1 and .85 at Time 2.…”
Section: Methodsmentioning
confidence: 99%